2022
DOI: 10.1039/d2nr05099d
|View full text |Cite
|
Sign up to set email alerts
|

In situ Cu single atoms anchoring on MOF-derived porous TiO2 for the efficient separation of photon-generated carriers and photocatalytic H2 evolution

Abstract: Single atom catalysts (SACs) have extremely high atom utilization and distinctive structures and properties in the field of photocatalysis. However, the premise of conducting scientific research and applications is still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Charge migration impedance is also one of the main factors affecting photocatalytic efficiency. 53 As discerned in Fig. 4d, MIL-68(In)-20@ZIS has a faster charge transfer process than pure ZIS.…”
Section: Resultsmentioning
confidence: 74%
“…Charge migration impedance is also one of the main factors affecting photocatalytic efficiency. 53 As discerned in Fig. 4d, MIL-68(In)-20@ZIS has a faster charge transfer process than pure ZIS.…”
Section: Resultsmentioning
confidence: 74%
“…Zhang et al 231 developed a CuSAā€“TiO 2 photocatalyst derived from MIL-125, which resulted in a H 2 precipitation rate of 101.7 mmol g āˆ’1 h āˆ’1 and achieved a quantum efficiency of 56% at 365 nm. In another study, 232 the same team mentioned that the coupling of Cu single atoms (Cu-SAs) with O atoms on the surface accelerated the transfer of photo-generated charge carriers from TiO 2 to Cu-SAs, ultimately increasing the rate of hydrogen evolution. Of course, the excellent hydrogen evolution activity is mainly due to the existence of copper single atoms capable of in situ self-healing and MOF carriers with a high specific surface, which facilitates effective charge separation.…”
Section: The Application Of Sacs Derived From Mofs In the Catalysis F...mentioning
confidence: 99%
“…In another study, Zhang et al 231 confirmed the presence of Cu atoms only in Ti vacancies by the HAADF-STEM method and also clarified the stability of Cu single atoms located on TiO 2 by comparing the HAADF-STEM of the catalyst after photocatalytic reaction, laterally responding to the porous nature of MIL-125 (Ti v ) and the strong anchoring of Cu ions by unsaturated bonds. Furthermore, Ma et al 232 analyzed the results by using XPS, XRD, and HAADF-STEM to conclude that Cu SAs in MOF-derived SACs replaced certain Ti atoms and were anchored by O atoms to produce +2 and +1 valences. HAADF-STEM, however, has flaws as well and is only appropriate for the examination of a few chosen places rather than the overall analysis of the samples.…”
Section: The Characterization Techniques Of Sacs Derived From Mofsmentioning
confidence: 99%
“…Cu single atoms presented very superior photocatalytic activity. 105 Cu single atoms with unsaturated coordination loaded in TiO 2 with oxygen vacancies, 106 and the adsorption of water molecules was facilitated and the hydrogen evolution activity of the photocatalyst was significantly improved. Zhang et al 95 introduced Cu into MIL-125 and then derived it into TiO 2 with anchored Cu single atoms, and it significantly enhanced the hydrogen evolution activity and the photocatalyst had excellent stability.…”
Section: Doping Metal Ions and Loading Cocatalysts To Mil-125mentioning
confidence: 99%